O acervo de obras raras biblioteca Arthur Vianna: o processo de digitalizaçao - PERGAMINELLIS, Marcelo Lopes (2019)
The research addresses the Arthur Vianna Public Library, where it promotes access to information for the general public. As a general objective of this research is to know the change from the physical format to the digital format of the library. And its methodology is descriptive in character and two "quali-quanti" methods were used. The data were collected by an interview guide applied to the members of the "Rare and Ancient Works Project -Digital Collection" where the Library is inserted. From the field research the importance of the rare works sector was observed, due to its historical and cultural value, and by the process of digitizing them for access to the digital collection.